Endotracheal tube cuff pressure: need for precise measurement - Braz, José Reinaldo Cerqueira; Navarro, Lais Helena Camacho; Takata, Ieda Harumi; Nascimento Júnior, Paulo (São Paulo Medical Journal, 1999)
CONTEXT: High compliance endotracheal tubes cuffs are used to prevent gas leak and also pulmonary aspiration in mechanically ventilated patients. However, the use of the usual cuff inflation volumes may cause tracheal damage. OBJECTIVE: We tested the hypothesis that endotracheal tube cuff pressures are routinely high (above 40 cmH2O) in the Post Anesthesia Care Unit (PACU) or Intensive Care Units (ICU). DESIGN: Cross-sectional study. SETTING: Post anesthesia care unit and intensive care unit. PARTICIPANTS: We measured endotracheal tubes cuff pressure in 85 adult patients, as follows: G1 (n = 31) patients from the ICU; G2 (n = 32) patients from the PACU, after anesthesia with nitrous oxide; G3 (n = 22) patients from the PACU, after anesthesia without nitrous oxide. Intracuff pressure was measured using a manometer (Mallinckrodt, USA). Gas was removed as necessary to adjust cuff pressure to 30 cmH2O. MAIN MEASUREMENTS: Endotracheal tube cuff pressure. RESULTS: High cuff pressure (> 40 cmH2O) was observed in 90.6% patients of G2, 54.8% of G1 and 45.4% of G3 (P < 0.001). The volume removed from the cuff in G2 was higher than G3 (P < 0.05). CONCLUSION: Endotracheal tubes cuff pressures in ICU and PACU are routinely high and significant higher when nitrous oxide is used. Endotracheal tubes cuff pressure should be routinely measured to minimize tracheal trauma.